Combined Bioremediation of Bensulfuron-Methyl Contaminated Soils With Arbuscular Mycorrhizal Fungus and Hansschlegelia zhihuaiae S113 - Qian, Yingying; Zhao, Guoqiang; Zhou, Jing; Zhao, Huazhu; Mutter, Thamer Y.; Huang, Xing (Frontiers in Microbiology, 2022)
Over the past decades, because of large-scale bensulfuron-methyl (BSM) application, environmental residues of BSM have massively increased, causing severe toxicity in rotation-sensitive crops. The removal of BSM from the environment has become essential. In this study, the combined bioremediation of the arbuscular mycorrhizal fungi (AMF) Rhizophagus intraradices and BSM-degrading strain Hansschlegelia zhihuaiae S113 of BSM-polluted soil was investigated. Both S113 and AMF coexist-ed in rhizosphere soil. BSM degradation by S113 in the maize rhizosphere could better promote AMF infection in the roots of maize, achieving an infection rate of 86.70% on the 36th day in the AMF+S113+BSM group. Similarly, AMF partially enhanced the colonization and survival of S113 in maize rhizosphere, contributing 4.65×105 cells/g soil on the 15th day and 3.78×104 cells/g soil on the 20th day to a population of colonized-S113 (based on the strong root system established by promoting plant-growth AMF). The BSM-degrading strain S113 could completely re-move BSM at 3 mg/kg from the maize rhizosphere soil within 12 days. AMF also promoted the growth of maize seedlings. When planted in BSM-contaminated soil, maize roots had a fresh weight of 2.59 ± 0.26 g in group S113+AMF, 2.54 ± 0.20 g in group S113+AMF+BSM, and 2.61 ± 0.25 g in the AMF group, all of which exceeded weights of the control group on the 36th day. Additionally, high-throughput sequencing results indicated that simultaneous inoculation with AMF and strain S113 of BSM-polluted maize root-soil almost left the indigenous bacterial community diversity and richness in maize rhizosphere soil unaltered. This represents a major advantage of bioremediation approaches resulting from the existing vital interactions among local microorganisms and plants in the soil. These findings may provide theoretical guidance for utilizing novel joint-bioremediation technologies, and constitute an important contribution to environmental pollution bioremediation while simultaneously ensuring crop safety and yield.